Global auteur the politics of authorship in 21st century cinema - Jeong, Seung-hoon; Szaniawski, Jeremi (New York Bloomsbury, 2016)
"A thorough and robust reassessment of the auteur figure in the age of global cinema"--
Includes bibliographical references and index.
Keywords: Auteur theory (Motion pictures); Motion pictures -- Production and direction; Motion pictures -- 21st century -- History and criticism; PERFORMING ARTS / Film & Video / History & Criticism; PERFORMING ARTS / Film & Video / Direction & Production